2017
DOI: 10.1212/wnl.0000000000004179
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegenerative and psychiatric diseases among families with amyotrophic lateral sclerosis

Abstract: Objective:To estimate risks of neurodegenerative and psychiatric diseases among patients with amyotrophic lateral sclerosis (ALS) and their families.Methods:We conducted a register-based nested case-control study during 1990–2013 in Sweden to assess whether patients with ALS had higher risks of other neurodegenerative and psychiatric diseases before diagnosis. We included 3,648 patients with ALS and 36,480 age-, sex-, and county of birth–matched population controls. We further conducted a follow-up study of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 35 publications
2
46
0
1
Order By: Relevance
“…This resulted in small numbers in some analyses; therefore, these results should be interpreted cautiously. We were unable to examine associations with psychosis, schizophrenia or autism, and neuropsychiatric disorders, which have been shown to occur at higher rates in MND kindreds 11 14 15. The number of patients with neuropsychiatric medication was higher than those with a neuropsychiatric history (127 vs 60).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This resulted in small numbers in some analyses; therefore, these results should be interpreted cautiously. We were unable to examine associations with psychosis, schizophrenia or autism, and neuropsychiatric disorders, which have been shown to occur at higher rates in MND kindreds 11 14 15. The number of patients with neuropsychiatric medication was higher than those with a neuropsychiatric history (127 vs 60).…”
Section: Discussionmentioning
confidence: 93%
“…An association between neuropsychiatric disorders and ALS has previously been shown 9 10. Neuropsychiatric symptoms including schizophrenia, depression, anxiety, and drug abuse or dependence are common in the years prior to and following diagnosis in both ALS10 11 and behavioural-variant FTD 12. Genome-wide association studies have revealed a modest genetic correlation between schizophrenia and ALS 13.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…A Swedish national registry study, which identified 3,648 ALS cases and 364,800 matched controls found higher rates of psychiatric disorders in children of those with ALS. 31 The overlap between ALS and schizophrenia is unlikely to be attributed to C9orf72 mutations Abbreviations: ALS = amyotrophic lateral sclerosis; MI = myocardial infarction; RR = risk ratio. Note 0.5 was added to the case count for anorexia to enable estimation of the RR.…”
Section: Discussionmentioning
confidence: 99%
“…11 This suggests that these diseases may cluster with pedigrees, like other neurodegenerative diseases. 34,35 The fact that patients develop severe bulbar symptoms with respiratory insufficiency (reminiscent of ALS) and may develop cognitive and behavioral changes within the FTD spectrum supports considering FOSMN as part of the FTD-Multiple lines of evidence seem to support the hypothesis that FOSMN is a neurodegenerative disorder.…”
Section: Cases With a Positive Family History Of Als/ftd-als 11mentioning
confidence: 98%